Climate change and food safety - Ariño A. (Food safety challenges for mediterranean products, 2015)
Worldwide, climate change is already affecting the biology and ecology of some organisms because of changing patterns in crop production and livestock intensification, as well as altering the transport pathways of chemical contaminants. Consequently, climate change is expected to aggravate feed and food safety problems during all phases of food production and supply. Temperature increases and changes in rainfall patterns will have an impact on the persistence and patterns of occurrence of bacteria, viruses, parasites, fungi, and harmful algae and the patterns of their corresponding foodborne diseases and the risk of toxic contamination. Chemical residues of pesticides and veterinary medicines in plant and animal products will be affected by changes in pest pressure. The food risks of heavy metals and persistent organic pollutants (i.e. dioxins, polychlorinated biphenyls) could rise following changes in soils and long-range atmospheric transport, though quantitative estimates are scarce. This short review presents data on the effect of climate change on biological and chemical food safety hazards, as well as it discusses the need for scientific research and development of improved tools, techniques and practices to adapt the current risk management systems.
Workshop Food Safety Challenges for Mediterranean Products, 2014/06/10-11, Zaragoza (Spain)